2022
DOI: 10.1037/trm0000357
|View full text |Cite
|
Sign up to set email alerts
|

Disparate effects of BP Deepwater Horizon oil spill exposure on psychological resilience.

Abstract: A growing body of research has demonstrated links between exposure to the BP Deepwater Horizon oil spill (DHOS) and negative consequences for well-being in the impacted region. We contribute to this literature by investigating the relationship between exposure to the DHOS (i.e., physical and economic) and subsequent perceptions of the ability to cope with adverse events (i.e., psychological resilience) among adults with children. Doing so advances prior research by (a) providing a direct test of psychological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…These results are consistent with previous findings from studies examining associations between oil exposure and acute mental health impacts [ 11 , 18 , 22 , 33 , 34 ]. The implications for longer-term mental health are unclear; one recent study found that physical exposure to the Deepwater Horizon Oil Spill was not associated with measures of psychological resiliency for several years among adults with children [ 35 ], while another study found that later mental health in the community might be a function of cumulative exposure to other disasters as well (e.g., Hurricane Katrina) not only the Deepwater Horizon Oil Spill [ 36 ]. Our findings that exposed individuals with lower self-mastery scores had greater mental health impacts also agree with studies demonstrating the positive associations between high levels of self-mastery and improved mental health [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with previous findings from studies examining associations between oil exposure and acute mental health impacts [ 11 , 18 , 22 , 33 , 34 ]. The implications for longer-term mental health are unclear; one recent study found that physical exposure to the Deepwater Horizon Oil Spill was not associated with measures of psychological resiliency for several years among adults with children [ 35 ], while another study found that later mental health in the community might be a function of cumulative exposure to other disasters as well (e.g., Hurricane Katrina) not only the Deepwater Horizon Oil Spill [ 36 ]. Our findings that exposed individuals with lower self-mastery scores had greater mental health impacts also agree with studies demonstrating the positive associations between high levels of self-mastery and improved mental health [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Most population-based research has used cross-sectional data to study health in the context of the DHOS, an important shortcoming because technological disasters can have health impacts spanning years. [2][3][4][5] Few panel studies exist and even fewer cover more than 1 or 2 years, thus, much remains unknown about the long-term DHOS effects on health. [6][7][8][9] Exceptions include a panel study of women following the DHOS which found ongoing elevated symptoms of depression and mental distress up to 6 years following the spill.…”
Section: Introductionmentioning
confidence: 99%